Compliant rebels : rebel groups and international law in world politics - Jo, Hyeran, 1976- (Problems of international politics., 2015)
Seventeen million people have died in civil wars and rebel violence has disrupted the lives of millions more. In a fascinating contribution to the active literature on civil wars, this book finds that some contemporary rebel groups actually comply with international law amid the brutality of civil conflicts around the world. Rather than celebrating the existence of compliant rebels, the author traces the cause of this phenomenon and argues that compliant rebels emerge when rebel groups seek legitimacy in the eyes of domestic and international audiences that care about humanitarian consequences and human rights. By examining rebel groups' different behaviors such as civilian killing, child soldiering, and allowing access to detention centers, Compliant Rebels offers key messages and policy lessons about engaging rebel groups with an eye toward reducing civilian suffering in war zones.